Ocular Burkholderia pseudomallei, a rare variant in presentation – A case series - Saidatulakma Sharif; Muhammad Ikmal Mohamad Kamil; Wan Norliza Wan Muda; Akmal Haliza Zamli; Khairy Shamel Sonny Teo; Liza Sharmini Ahmad Tajudin (Medical Communications, 2020)
Burkholderia pseudomallei is Gram-negative anaerobe causing melioidosis. We report a case series including three cases of rare ocular presentations in patients with positive melioidosis serology in the state of Pahang, Malaysia. The first case involved a 32-year-old male with a sudden onset of painless decrease in vision in the left eye, with a history of swimming in a river. Eye examination revealed a choroidal abscess with inferior retinal detachment. The second case was that of a 14 year-old-male patient with painless reduction of vision in the left eye and a history of parotid gland swelling. Eye fundus examination showed optic disc swelling with macular star. The third case, a 10-year-old male, presented with left eye optic disc granuloma and subtotal exudative retinal detachment with vasculitis. The three cases were successfully treated with the antibiotic ceftazidime. Ocular melioidosis should always be taken into consideration in any patient with suspected infectious uveitis. A high index of suspicion is required to initiate early and prompt treatment.